Opportunities and Challenges for Achieving Land Degradation Neutrality in the Forest Sector - Rawat, R.S.; Gautam, Shilpa (Indian Forester, 2022)
Forests are among the most biodiverse ecosystems and play a major role in mitigating climate change and providing livelihood opportunities to the forest fringe communities. Relevant policies, laws and regulations, ongoing forestry programmes and projects for conservation and sustainable management of forests as well as for meeting the national targets and international commitments across the country provides enabling environment for achieving land degradation neutrality in the forest sector. Main challenges identified for achieving land degradation neutrality in the forest sector are no coordination mechanism among the institutions dealing the issues related to land, poor linkages between financial institutional and forestry institutions, non-availability of sufficient finance for restoration of degraded forest lands, lack of capacity of stakeholders for dealing the issue and no specific responsibility of the corporate sector in restoration of degraded forest lands. Besides addressing these challenges, setting up of state-specific land degradation neutrality targets and transformative projects need to be implemented for restoration of degraded forests and achieving land degradation neutrality.